The development of educational personnel - ภมโร พระครูอุทุมพรกิตติคุณ (Journal of Educational Review Faculty of Education in MCU, 2018)
Education is a vital and necessary for everyone, especially the worldly education is for living a life and surviving family, subordinates and relatives. Religious education is for realizing what is good or bad, what should be done and avoided. In brief, religious education is for liberate oneself from the Round of Rebirth and for attaining Nibbana. Education develops human’s knowledge, ability, intellectual and thinking. Creative thinking must be accompanied by Dhamma or otherwise that thinking can cause troubles. Personnel in education must have Dhamma to frame their thinking, knowledge, doing and speaking in goodness. The Dhamma necessary in training educational personnel is the Threefold Training: Morality, Mentality and Wisdom.